On the Diffusion of Computer Terminals in an Established Engineering Environment - Randles, F. (Management Science, 1983)
The introduction of new technologies in existing administrative and technical organizations usually represents a significant investment in equipment and training. A prudent manager will attempt to acquire the equipment needed fast enough to encourage its use while avoiding the inefficiencies of under-utilization. This paper presents a method of applying a mathematical model to the specific problem of predicting the approximate rate at which additional computer terminals should be acquired. The model used is in the form of a “logistics” or “diffusion” function. To apply the model to the Aerospace division of a company, a “calibration” of that organization was required. A questionnaire on the use of hand calculators was submitted to a sample group. At the time of the study, hand calculators had virtually displaced slide rules and desk top adding machines, and about 15 percent of the organization was competing for available terminals of the central computer system. Increased use of terminals and on-line computing was anticipated. The response of the organization to the hand calculator innovation was established by determining a “logistics” or “diffusion” function to fit the sample data. The function was modified to accommodate the additional complexity of the more sophisticated computational capability and then used to predict terminal requirements. This study was undertaken to satisfy a management need to plan for its investment in terminals. At the introduction of an interactive computing system, terminals were requested for individuals or projects. As the number of terminals increased, the number of qualifed users increased faster, and requests for terminals became more numerous. Justifications frequently appeared to be overlapping or duplicative. At this point, a better perspective of the money needed was required, and the study was initiated. The results of the study, together with user requirements data, have been used to expedite the acquisition of terminals.